Odrzańska droga wodna na obszarze województwa zachodniopomorskiego 2001 = The Odra River water-way in the region of west pomerania voivodeship - Wira, Jerzy; Tarnowski, Krzysztof; Kowalski, Piotr; Urban, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Odra River water-way is one of the most important water-ways in Poland. It has convenient possibilities for connection with net of waterways in Poland and also with European system of water-ways. The characteristic of Odra River water-way in the West Pomerania Voivodeship and possibilities of its development were presented in the paper.
Keywords: Odrzańska droga wodna; Zachodniopomorskie (województwo)